RELATIONSHIP OF SELF EFFICACY WITH SELF REGULATED LEARNING STUDENTS OF SMA N 1 LUBUK BASUNG - Sinta Huri Amelia; Taufik Taufik (Universitas Negeri Padang, 2021)
Ideally a student has good self-efficacy and self-regulated learning. Today it is found that students do not focus and concentrate in learning activities and doing assignments because of a lack of self-regulation in learning. This study aims to reveal (1) students' self-efficacy, (2) students' self-regulated learning, (3) to test the significant level of the relationship between students' self-efficacy and self-regulated learning. This research is a quantitative study with a correlational descriptive method. The study population was 955 students of SMA N 1 Lubuk Basung who were registered in the 2020/2021 school year. The number of samples is 285 students, obtained by using the Stratified Random Sampling technique. The instrument used was a questionnaire about self-efficacy and self-regulated learning with a Likert scale model. The data analysis technique used is descriptive technique using the percentage formula to see a picture of self-efficacy and self-regulated learning. Meanwhile, to test the significant level of the relationship between self-efficacy and self-regulated learning, the Pearson Product Moment Correlations formula is used. The research results reveal that; (1) the overall student self-efficacy is in the medium category (2) overall self-regulated learning is in the medium category (3) and there is a significant positive relationship between student self-efficacy and self-regulated learning with a r table of 0.113 and r count of 0.674 significant level of 0.000. This means that the higher the self-efficacy, the higher the students' self regulated learning.